American College of Rheumatology White Paper on Performance Outcome Measures in Rheumatology. Issue 10 (16th September 2016) - Suter, Lisa G.; Barber, Claire E.; Herrin, Jeph; Leong, Amye; Losina, Elena; Miller, Amy; Newman, Eric; Robbins, Mark; Tory, Heather; Yazdany, Jinoos
Abstract : Objective: To highlight the opportunities and challenges of developing and implementing performance outcome measures in rheumatology for accountability purposes. Methods: We constructed a hypothetical performance outcome measure to demonstrate the benefits and challenges of designing quality measures that assess patient outcomes. We defined the data source, measure cohort, reporting period, period at risk, measure outcome, outcome attribution, risk adjustment, reliability and validity, and reporting approach. We discussed outcome measure challenges specific to rheumatology and to fields where patients have predominantly chronic, complex, ambulatory care–sensitive conditions. Results: Our hypothetical outcome measure was a measure of rheumatoid arthritis disease activity intended for evaluating Accountable Care Organization performance. We summarized the components, benefits, challenges, and tradeoffs between feasibility and usability. We highlighted how different measure applications, such as for rapid cycle quality improvement efforts versus pay for performance programs, require different approaches to measure development and testing. We provided a summary table of key take‐home points for clinicians and policymakers. Conclusion: Performance outcome measures are coming to rheumatology, and the most effective and meaningful measures can only be created through the close collaboration of patients, providers, measure developers, and policymakers. This study provides an overview of key issues and is intended to stimulate a productive dialogue between patients, practitioners, insurers, and government agencies regarding optimal performance outcome measure development.